The Treatment of a Patient with Type 1 Diabetes and Allergy to Titanium Dental Implants from Zircon Oxide Ceramics - R. Šmucler (Česká Stomatologie a Praktické Zubní Lékařství, 2008)
The objective of the work was to describe an unusual case report of a patient with Type 1 diabetes, who eliminated the primarily stable titanium implants (within the time lapse of several weeks after lege artis - performed operation) due to multiple allergy to metals and was later treated with ceramic implants on the basis of zirconium oxide (ZrO₂). Later on the patient was treated with immediate fixed splint composite bridge. Six months later the prosthetic work was taken off, stability of the healed implants was measured and a final treatment was performed using an all-ceramic fixed splint bridge from a zirconium ceramic. This rare case history will be difficult to verify by sufficiently randomized group in view of the scarceness as indicated by lacking available world literature. If such conclusion may be drawn from this rare case, the treatment of a patient with allergy to titanium and Type 1 diabetes with zirconium oxide implants appear to be a possible therapeutic alternative.